Hubungan Urinalisis (Leukosit dan Nitrit) dengan Kultur Urin untuk Deteksi Infeksi Saluran Kemih (ISK) di RSUD dr Pirngadi Medan Periode Juli 2024 – Juni 2025 - Renatha Nainggolan; Thomas Silangit; Budi Sembiring; Marlina Rajagukguk; Nova Rajagukguk; Ronald T. H. Tambunan (Universitas Methodist Indonesia, 2025)
Urinalysis is a basic test for patients with urinary tract infections (UTIs). Ninety-five percent of UTIs are caused by E. coli. The incidence rate of UTIs in Indonesia among adolescents aged 10-18 years is 35%-42%, and among young adults aged 19-22 years, it is 27%-33%. UTI diagnosis is confirmed by urine culture, where a bacterial count of > 10⁵ colonies per milliliter (CFU/ml) is detected. The urinalysis shows leukocyturia and a positive nitrite test. Bacteria capable of converting nitrate to nitrite include Escherichia coli, Enterobacter, Citrobacter, Klebsiella, and Proteus species. This study used an observational analytical study with a cross-sectional design and retrospective approach. The study sample consisted of UTI patients who underwent leukocyte, nitrite, and urine culture tests recorded in the medical records of the Clinical Pathology Department at Dr. Pirngadi General Hospital in Medan. Out of 60 urine culture samples, 12 samples showed no bacterial growth. The results showed that the majority of UTI patients were female, totaling 36 individuals (60%), compared to 24 males (40%). The age group of 51-70 years (54%) had the highest number of UTI patients. Positive leukocytes experienced UTI (68.8%) compared to negative leukocytes (p-value 0.001). Compared to negative nitrites, 58.3% of positive nitrites had a UTI (p-value 0.001). In this study, the most common bacteria causing UTI were Klebsiella pneumoniae (43%), Enterococcus faecalis (17%), and Escherichia coli (8%). In 60 urine culture samples, the most common bacteria causing UTIs were Klebsiella pneumoniae (43%), Enterococcus faecalis (17%), and Escherichia coli (8%). Leukocytes were positive in 68.8% of cases of UTI compared to negative leukocytes, with a p-value of 0.001. Nitrites were positive in 58.3% of cases of UTI compared to negative nitrites, with a p-value of 0.001.